Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1051/e3sconf/20171700009
|View full text |Cite
|
Sign up to set email alerts
|

The content of heavy metals in soils and plants around the waste landfill in Siechnice (Poland)

Abstract: Abstract. Metal concentrations (Cu, Zn, Pb, Ni, Cr) in soils and plants around the metallurgical waste landfill of Siechnice, Poland, have been determined. The soil samples were collected from the surface layer of 0-25 cm. The soils and plants were digested in HNO 3 , 60%, using the Microwave Digestion System (Milestone Start D). The analysis of metals has been carried out through the Flame Atomic Absorption Spectroscopy (FAAS) method. The pH and the conductivity of the soil solutions were measured. The pollu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…For Zn, the concentration is 47.65, which is 1.78 times higher than our results for the control sample. The highest exceedance occurs in the Pb concentration, as the difference between the control sample obtained in this study and the samples from the study Borowczak and Hołtra [Borowczak, Hołtra, 2017] is 6.67 times higher. This suggests that taking a zero sample should be restricted to the areas far away from any industries and roads, as they also affect soil contamination.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…For Zn, the concentration is 47.65, which is 1.78 times higher than our results for the control sample. The highest exceedance occurs in the Pb concentration, as the difference between the control sample obtained in this study and the samples from the study Borowczak and Hołtra [Borowczak, Hołtra, 2017] is 6.67 times higher. This suggests that taking a zero sample should be restricted to the areas far away from any industries and roads, as they also affect soil contamination.…”
Section: Discussionmentioning
confidence: 49%
“…The high values of the elements in the control soil may result from the fact that this sample was taken near the main road from/ to Wrocław and from the possible influence of industries located there, which deal with laser cutting, electro-technical industry and service of French cars etc. In the publication of Borowczak and Hołtra [Borowczak, Hołtra, 2017], the control sample was taken at three sites from a cultivated field in Siechnice, where the concentration of Cu was 10.14 mg/kg, which indicates that the concentration in the control sample is 7.6 times higher. For Zn, the concentration is 47.65, which is 1.78 times higher than our results for the control sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cr Residual sludge tannery [35] Cd, Cu, Fe, and Pb Compost leach [38] As, Cd, Ni, Pb, and Zn Ash remediation [28] Al, Cr, Cu, Fe, Mn, Ni, and Zn Rehabilitation of iron mine [13] Cu, Fe, Mn, Pb, and Zn Water polluted with heavy metals [12] Cr, Cu, Pb, and Zn Soil contaminated with heavy metals [38] Cu, Fe, Mn, Pb, and Zn Industrial waters [24] B Industrial waters [37] grass, the findings of different studies have confirmed the potential of vetiver as a phytoremediation plant for use in the removal of heavy metals from contaminated soils [12,46,47] and in the rehabilitation of landfills [36]. Although it is not an aquatic plant, vetiver can grow and survive under hydroponic conditions [48] and can be used to remediate eutrophic waters, wastewater from pig farms [49], and waste leachates [50].…”
Section: Heavy Metals Origin Referencesmentioning
confidence: 99%